Avaliação da alteração da temperatura pulpar in vitro em dente restaurado com resinas bulk-fill utilizando diferentes estratégias de fotoativação - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
The aim of this in vitro study was to assess the temperature range within pulp chamber during different strategies of photoactivation of bulk fill composites placed in a Class I cavity preparation. After the approval by the local Ethics Committee, one third molar donated by the Human Teeth Bank of UEPG had its roots sectioned and the root canals enlarged. The tooth was fixed in an acrylic plaque with perforations and it was fixed in a temperature analysis device coupled to the tooth by T-type thermocouples, connected in a temperature analysis system (Thermes, Phisytemp). The temperature inside the pulpal chamber was evaluated in real time during composite insertion and photoactivation of the bulk fill composites Tetric N Ceram Bulk FIll (TBF - Ivoclar Vivadent) e Surefill SDR flow + (SDR - Dentsply Sirona). The bulk fill composites were exposed to different exposure strategies using a Polywave light-curing unit (Bluephase N, Ivoclar Vivadent). The bulk, polymerized resin composite increments were removed from the cavity preparation and were sectioned to expose the flat, middle center internal surface, which was polished. Vickers hardness test (VHN) was also performed in triplicate on the top and bottom of the restorations. Temperature and Vickers hardness data were analyzed by 2-way ANOVA followed by Bonferroni test (alpha = 0,05) and peak temperature results were analyzed by 2-way ANOVA followed by Dunnet’s test. The top/bottom hardness ratio was evaluated, for TBF, by Welch test for groups without homogeneity of variance and, for SDR, one-way ANOVA. SDR had higher peak temperature values than TBF. For SDR, the 10 seconds for buccal, followed by 10 seconds for lingual and 20 seconds for occlusal technique caused higher temperature variation values. The top hardness of both composites was higher than the bottom. Neither technique caused a temperature increase greater than the threshold temperature rise of 5.5 °C and both composites had acceptable top/bottom hardness ratios, regardless of photoactivation strategy.
Keywords: Resinas Compostas; Polimerização; Polpa Dentária; Composite Resins; Polymerization; Dental Pulp; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA